Study on Magnetic Abrasive Finishing of Brass Rods Using SiC-Based Abrasives - Goyal, Amit; G. Kaushal (Asian Review of Mechanical Engineering, 2014)
Magnetic Abrasive Finishing (MAF) process is one of the advanced machining processes for finishing non-ferrous materials, in which the cutting force is controlled by input current to the magnetic coils. MAF set-up was designed and mounted on the lathe machine for finishing CuZn37 brass rods. Effect of different process parameters (current, rotational speed and percentage composition of abrasives) is evaluated by using Taguchi experimental design and further the most critical parameter for finishing CuZn37 is determined by using MINITAB software. The results along with observations are discussed in detail in the present study. Based upon the results, circumferential speed of the workpiece is very useful parameter in improving the surface roughness. The change in surface roughness increases by increasing circumferential speed in magnetic abrasive finishing process